I tried to solve this for hours but no success.

Prove that the arithmetic mean is less or equal than the quadratic mean.

I am in front of this form: $$ \left(\frac{a_1 + ... + a_n} { n}\right)^2 \le \frac{a_1^2 + ... + a_n^2}{n} $$

With rewriting the inequality in other forms I had no luck.

I think maybe induction would be OK, but I have no idea, how to do it in this case. Do you know a good proof for this?



The result is immediate if all the $a_i$ are zero, so we may assume that not all $a_i$ are zero. Further, by the triangle inequality, $\lvert\frac{a_1 + \cdots + a_n}{n}\rvert \le \frac{\lvert a_1\rvert + \cdots + \lvert a_n\rvert}{n}$. Therefore $\left(\frac{a_1 + \cdots + a_n}{n}\right)^2 \le \left(\frac{\lvert a_1\rvert + \cdots + \lvert a_n\rvert}{n}\right)^2$. So we may suppose additionally that all the $a_i$ are nonnegative.

Introduce a discrete random variable $X$ on the sample space $\{a_1,\ldots, a_n\}$ by letting $P(X = a_i) = a_i/n$ for $i = 1,2,\ldots n$. Then mean of $X$ is $\mu = (a_1 + \cdots + a_n)/n$, so the variance of $X$ is $$\operatorname{var}(X) = E(X^2) - \mu^2 = \left(\frac{a_1^2 + \cdots + a_n^2}{n}\right) - \left(\frac{a_1 + \cdots + a_n}{n}\right)^2$$ Since the variance is nonnegative, we deduce that $$\left(\frac{a_1 + \cdots + a_n}{n}\right)^2 \le \frac{a_1^2 + \cdots + a_n^2}{n}$$

  • $\begingroup$ could you please explain it a bit more in detail? just the beginning, the P, maybe if you would write it in words? $\endgroup$ – user3435407 Feb 1 '15 at 19:59
  • $\begingroup$ Sure, but where are you having trouble? $\endgroup$ – kobe Feb 1 '15 at 20:00
  • $\begingroup$ "by letting P(X=ai)=ai/(a1+⋯+an) for i=1,2,…n" $\endgroup$ – user3435407 Feb 1 '15 at 20:01
  • $\begingroup$ By letting $P(X = a_i) = a_i/(a_1 + \cdots + a_n)$ for each $i$, we have $P(X = a_1) + \cdots P(X = a_n) = 1$, so the function $f(x) = P(X = x)$ is the probability mass function of $X$. $\endgroup$ – kobe Feb 1 '15 at 20:06
  • 1
    $\begingroup$ I finished the task and i am very glad about it, and this proof is the most elegant proof of all time, i love it, thanks again! :) $\endgroup$ – user3435407 Feb 1 '15 at 23:18

By Cauchy–Schwarz inequality, $$\left(\frac{a_1}{n}1+\frac{a_2}{n}1+\cdots+\frac{a_n}{n}1\right)^2\le\left(\frac{a_1^2}{n^2}+\frac{a_2^2}{n^2}+\cdots+\frac{a_n^2}{n^2}\right)\left(1^2+1^2+\cdots+1^2\right)$$


Let $f(x) = x^2$. Since $f''(x) = 2 > 0$, $f$ is convex. Thus \begin{align*} f\left(\frac{x_1+x_2+\cdots + x_n}{n}\right) \leq \frac{f(x_1)+f(x_2)+\cdots+f(x_n)}{n} \end{align*} In fact, considering the function $f(x) = x^{p/q}$, where $p > q>0$, one can show that \begin{align*} \left(\frac{x_1^q+x_2^q+\cdots +x_n^q}{n}\right)^{1/q} \leq \left(\frac{x_1^p+x_2^p+\cdots +x_n^p}{n}\right)^{1/p} \end{align*}


for sake of contradiction suppose:
$\sqrt{\frac{a_1^2+ \cdots +a_n^2}{n}}<\frac{a_1+ \cdots +a_n}{n}\\ \frac{a_1^2+ \cdots +a_n^2}{n}<\frac{(a_1+ \cdots +a_n)^2}{n^2}\\ \frac{a_1^2+ \cdots +a_n^2}{n}<\frac{a_1^2+ \cdots +a_n^2}{n^2}+2\frac{\sum_{sym}a_1a_2}{n^2}\\ \\ (n-1)(a_1^2+\cdots+a_n^2)<2\sum_{sym}a_1a_2 \quad \quad (1)$

At this point I show by induction that the last line is wrong:
$(n-1)(a_1^2+\cdots+a_n^2)\geq2\sum_{sym}a_1a_2 \quad \forall \:n\geq2, n\in \mathrm{Z^+}\\ \text{let} \quad n=2\\ (a_1-a_2)^2\geq0\\ a_1^2+a_2^2-2a_1a_2>0\\ \Rightarrow a_1^2+a_2^2\geq 2a_1a_2$
Now assume for $n=k$
$(k-1)(a_1^2+\cdots +a_n^2)\geq 2\sum_{sym}a_1a_2 \quad \quad (2)\\ \text{I have from the case $n=2$}\\ a_{k+1}^2+a_1^2\geq 2a_{k+1}a_1\\ \Rightarrow 2a_{k+1}^2+a_1^2+a_2^2\geq2a_{k+1}a_1+a_{k+1}^2+a_2^2\geq2a_{k+1}a_1+2a_{k+1}a_2\\\text{proceding as above}:\\ ka_{k+1}^2+a_1^2+\cdots+a_k^2 \geq 2 a_{k+1}(a_1+\cdots+a_k) \quad \quad (3)\\ \text{now adding (2) and (3):}\\ (k-1)(a_1^2+\cdots +a_k^2)+ka_{k+1}^2+a_1^2+\cdots +a_k^2\geq2\sum_{sym}a_1a_2+2a_{k+1}(a_1+\cdots +a_k)\\ \Rightarrow k(a_1^2+\cdots +a_{k+1}^2)\geq 2\sum_{sym}a_1a_2\\ \therefore (n-1)(a_1^2+\cdots+a_n^2)\geq2\sum_{sym}a_1a_2 \quad \forall \:n\geq2, n\in \mathrm{Z^+} \quad\text{by induction}$
This clearly contradicts (1), so I have:
$\sqrt{\frac{a_1^2+ \cdots +a_n^2}{n}}\geq\frac{a_1+ \cdots +a_n}{n}$
by contradiction.


This is kind of a simplistic and brute-force approach:

$$\bigg(\frac{\sum_{i = 1}^n a_i}{n}\bigg)^2 \leq \frac{\sum_{i=1}^n a_i^2}{n} \iff % \bigg(\sum_{i = 1}^n a_i\bigg)^2 \leq n \sum_{i=1}^n a_i^2$$

Now open the bracket on the left of the inequality and simplify and note that the result is equivalent to:

$$\sum_{1 \; \leq \; i \; < \; j \; \leq \; n} (a_i - a_j)^2 \geq 0$$

This is obvious.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.